DESCRIPTION OF CARIOMETHRIC INDEXES OF PAROTID SALIVARY GLAND’S EPITHELIOCYTES OF RATS IN NORM AND AT STIMULATION OF PROSERIN - Tsukanov, L.V.; Yeroshenko, G.A.; Gasyuk, N.V. (World of Medicine and Biology, 2012)
The cariomethric classes of epitheliocytes of end-pieces and striated ducts of parotid salivary glands are certain in a norm and at stimulation of proserine, which answer separate histogenetic types. Research confirms conception of the functional swelling of nucleuses, in obedience to which at the increase of the functional loading of nucleuses’ volume increases, and at diminishing goes down in 1,4 time.
Keywords: parotid gland; logarithm of volume; nucleus; stimulation